Modeling shear wave splitting due to stress-induced anisotropy, with an application to Mount Asama Volcano, Japan - Shelley, A.; Savage, M.; Williams, C.; Aoki, Y.; Gurevich, Boris (Wiley-Blackwell Publishing, 2014)
We use numerical modeling to investigate the proposed stress-based origin for changing anisotropy at Mount Asama Volcano, Japan. Stress-induced anisotropy occurs when deviatoric stress conditions are applied to rocks which are permeated by microcracks and compliant pore space, leading to an anisotropic distribution of open crack features. Changes to the local stress field around volcanoes can thus affect the anisotropy of the region. The 2004 eruption of Mount Asama Volcano coincided with time-varying shear wave splitting measurements, revealing changes in anisotropy that were attributed to stress changes associated with the eruption. To test this assertion, we create a model that incorporates knowledge of the volcanic stress, ray tracing, and estimation of the anisotropy to produce synthetic shear wave splitting results using a dyke stress model. Anisotropy is calculated in two ways, by considering a basic case of having uniform crack density and a case where the strength of anisotropy is related to dry crack closure from deviatoric stress. Our results show that this approach is sensitive to crack density, crack compliance, and the regional stress field, all of which are poorly constrained parameters. In the case of dry crack closure, results show that modeled stress conditions produce a much smaller degree of anisotropy than indicated by measurements. We propose that the source of anisotropy changes at Asama is tied to more complex processes that may precipitate from stress changes or other volcanic processes, such as the movement of pore fluid.